PERANCANGAN SISTEM PLAMBING PADA BANGUNAN WISMA MESS SEPOLWAN CIPUTAT - Ayo Pahpayungi; Hening Darpito; Mudarisin (JURNAL TECHLINK, 2022)
The construction of high-rise buildings in big cities is currently increasing rapidly, before the building is built, it is necessary to plan a plumbing system to meet the needs of water supply for daily needs in buildings and waste water disposal. In planning the plumbing of Wisma Mess Sepolwan 3 floors, the need for clean water is 28.92 m3/day, the GWT (Ground Water Tank) bottom tank capacity is 6.5 m3/day, the top tank capacity (Roof Tank) is 5.4 m3/day and the sewer tank 25 m3/day.The transfer of clean water from the ground water tank to the top water tank (roof tank) uses a transfer pump with a capacity of 5.4 m3/minute, pump head of 39.64 m. Fordistribution of clean water on 3 floors using a pressure booster pump with a capacity of 0.16 m3/minute and a pump head of 10.3 m.Transfer of clean water from the bottom water tank (Ground Water Tank) to the top water tank (Roof Tank) using a pipe size of 40 mm. The design of the diameter of the clean water distribution pipe for each floor gets a size of 150 mm diameter of the main pipe / water main pipe and 50 mm per floor.The design of the diameter of the sewerage pipe from (closet and toilet) size to the standpipe for each floor is 100 mm and the diameter of the riser standpipe is 150 mm. The design of the diameter of the waste water pipe from (hand sinks and traps) to the size of the standpipe for each floor is 80 mm and the diameter of the riser standpipe is 100 mm. The design of the vent pipe diameter for the size of the standpipe for each floor is 50 mm and the diameter of the riser standpipe is 80 mm